2016
DOI: 10.1007/s00520-016-3174-6
|View full text |Cite
|
Sign up to set email alerts
|

Early supportive medication use and end-of-life care among Medicare beneficiaries with advanced breast cancer

Abstract: Purpose A randomized controlled trial of cancer patients has linked early supportive care with improved hospice use and less aggressive end-of-life care. In practice, the early use of supportive interventions and potential impact on end-of-life care are poorly understood. We sought to describe early use of medications to treat common breast cancer symptoms (pain, insomnia, anxiety, and depression) and to assess the relationship between early use of these treatments and end-of-life care. Methods Secondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The medications captured through Part A/B claims represent medications administered; Part D claims represent medications prescribed and filled, which we refer to as medications received. Relevant symptom categories and individual drugs most commonly used to manage those symptoms were specified based on prior literature 30,31 and clinical guidelines 32 as well as input from clinicians on our team (see the Appendix Table 1 for complete classification of medications). Specifically, we identified medications used for pain (opioids, nonopioid analgesics, and adjuvants); emotional distress (antidepressants, anxiolytics/sedatives, and antipsychotics); fatigue (transfusions, erythropoietin-stimulating agents [ESAs], or methylphenidate); dyspnea (inhaled bronchodilators or corticosteroids, diuretics, oral chronic obstructive pulmonary disease or asthma medications, and secretion management medications); anorexia (appetite stimulants); and nausea/vomiting (serotonin [5hydroxytryptamine 3] antagonists, neurokinin-1 antagonists, prochlorperazine/promethazine, cannabinoids, and metoclopramide).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The medications captured through Part A/B claims represent medications administered; Part D claims represent medications prescribed and filled, which we refer to as medications received. Relevant symptom categories and individual drugs most commonly used to manage those symptoms were specified based on prior literature 30,31 and clinical guidelines 32 as well as input from clinicians on our team (see the Appendix Table 1 for complete classification of medications). Specifically, we identified medications used for pain (opioids, nonopioid analgesics, and adjuvants); emotional distress (antidepressants, anxiolytics/sedatives, and antipsychotics); fatigue (transfusions, erythropoietin-stimulating agents [ESAs], or methylphenidate); dyspnea (inhaled bronchodilators or corticosteroids, diuretics, oral chronic obstructive pulmonary disease or asthma medications, and secretion management medications); anorexia (appetite stimulants); and nausea/vomiting (serotonin [5hydroxytryptamine 3] antagonists, neurokinin-1 antagonists, prochlorperazine/promethazine, cannabinoids, and metoclopramide).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In the United States, in a cohort of 123 patients with metastatic BC, 53% died at home 23 and, in another cohort of 947 patients, 25% died in hospital. 5 The proportion of each place of death and the mode of management may vary according to the definition of the cases included, either people who died with a managed cancer or, inversely, people for whom a cancer was the main cause of death, the study period, but also according to age, the type of cancer, its stage and its history, and any comorbidities, including concomitant cancers and the development and organization of palliative care. [5][6][7][21][22][23][24][25][26][27][28][29][30][31][32][33] Observed frequencies also vary according to organization of end-of-life care or palliative care in each country, either mainly in short-stay hospitals, as in France, or by preferring discharge from hospital and management at home or in hospices.…”
Section: Place Of Deathmentioning
confidence: 99%
“…We categorized emotional symptom medications by antidepressants (excluding those already assigned to pain management), anxiolytics/sedatives, and antipsychotics. We identified relevant individual medications for pain and emotional distress based on input from the literature [23,30], clinical guidelines [31], and input from palliative care clinicians on the research team (Table S1). Once we identified the medications, we searched Part D claims for the study sample to identify the relevant generic drug names, including combinations identified by our clinical team.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…With ongoing efforts to improve the quality of cancer care, it is also important to examine older adults' use of prescription medication targeted at the management of pain and emotional distress. A number of studies have reported on receipt of supportive care medications, including opioids, non-opioids, antidepressants, and sleep aids by older adults with cancer [17][18][19][20][21][22][23][24]. However, relatively few studies have linked medication use to patient-reported symptoms (i.e.…”
mentioning
confidence: 99%